Role of fever and ambient temperature in COVID-19 - Muhammad Gul; Zin Mar Htun; Asad Inayat (2020)
Fever is one of the most preserved evolutionary response over 600 million years to infections in invertebrates, amphibians, reptiles, fish, and mammals [1]. It is a complex cytokine-mediated physio...